2012
DOI: 10.1002/jcop.21483
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Psychological Sense of LGBT Community Scale

Abstract: The focus of this study was the development and validation of a Psychological Sense of LGBT Community Scale (PSOC‐LGBT), designed to assess the degree to which self‐identified lesbian, gay, bisexual, and transgender (LGBT) persons report feelings of belonging to and being able to depend on their local LGBT community, as well as the degree to which they believe an LGBT community exists in their local area. The scale is a modification of an existing Psychological Sense of Community Scale (PSOCS) that was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 19 publications
1
49
0
Order By: Relevance
“…On the other hand, Peterson et al () have developed a scale that supports McMillan and Chavis’ () four‐dimensional PSC model, and Wombacher, Tagg, Bürgi, and MacBryde () and Barati et al () have provided strong support for the Peterson et al scale. Likewise, Lin and Israel's () exploratory approach actually revealed a model consistent with McMillan and Chavis’ original model. Also, Mannarini and Fedi's (2009) qualitative study revealed dimensions of PSC that support McMillan and Chavis’ model.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…On the other hand, Peterson et al () have developed a scale that supports McMillan and Chavis’ () four‐dimensional PSC model, and Wombacher, Tagg, Bürgi, and MacBryde () and Barati et al () have provided strong support for the Peterson et al scale. Likewise, Lin and Israel's () exploratory approach actually revealed a model consistent with McMillan and Chavis’ original model. Also, Mannarini and Fedi's (2009) qualitative study revealed dimensions of PSC that support McMillan and Chavis’ model.…”
Section: Resultsmentioning
confidence: 61%
“…A very important exception is Peterson et al's () 8‐item Brief Sense of Community Scale (BSCS), which was tested and confirmed in Wombacher et al (). Barati, Samah, & Ahmad () provided further evidence of the BSCS's validity by showing it is correlated with citizen participation. Similarly, Lin & Israel's () effort to test Proescholdbell et al's () 17‐item sense of community scale falls into the same category as Chipuer and Pretty (1999). Because Proescholdbell et al offered a specific model, Lin and Israel should have used a confirmatory rather than an exploratory approach, and so have not really attempted a replication of Proescholdbell et al's model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The functional property of the social network focuses on living arrangement, contact frequency with various types of social ties, and aspects of providing or receiving informal caregiving. We also include measures of general social participation (e.g., spiritual or religious activities, club meetings or group activities, and volunteering) as well as LGBT-specific community engagement including sense of belonging, participating in social activities and community activism, and contributing to the community (Frost & Meyer, 2012;Lin & Israel, 2012).…”
Section: Social Factorsmentioning
confidence: 99%
“…The higher rates of depression and psychological distress among LGB persons may be attributed in part to experiencing discrimination, harassment, and victimization because of their sexual orientation. The findings that SMU may be a protective factor articulates the argument of sense of LGBTQ community, which suggests that belonging to a larger community may buffer effects of marginalization [52,53]. In terms of SM, being connected to other LGBTQ individuals may reduce the psychological effects of discrimination, harassment, and victimization these persons experience in the social environment.…”
Section: Discussion Principal Resultsmentioning
confidence: 84%